Metaverse vs Classroom: A Quasi-Experimental Study on Learning Digital Business and Creative Skills - Hanif Ksatria Faza; Btari Mariska Purwaamijaya; Muhammad Dzikri Ar Ridlo (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2025)
To address the need for practical skills in the creator economy era, this study evaluates the comparative effectiveness of Metaverse Based Learning, Online Learning, and Blended Learning models on students' cognitive competence. This study fills a crucial research gap by providing a quasi-experimental comparison within a developing country context, where technical constraints are a critical variable. Employing a mixed-methods approach anchored in a quasi-experimental pretest-posttest non-equivalent control group design (N = 90), data were collected using a validated cognitive competency test (α = 0.796) administered as a pre/post-test, supplemented by participant observation and semi-structured interviews. Quantitative data were analyzed using N-Gain and ANCOVA, while qualitative data were analyzed thematically. The results revealed a paradox: quantitatively, there was no statistically significant difference (p = .376) among the groups, with all models proving equally effective (N-Gain "High" category). However, qualitative findings consistently revealed that Metaverse Based Lerning was fundamentally superior in fostering interaction, active participation, and spontaneous creativity not observed in the other groups. The implication is that while all three models are equivalent for standard knowledge acquisition, Metaverse Based Learning offers a far superior potential for developing active and creative learners, a potential that was likely suppressed by technical constraints and not captured by the standard cognitive test.Keywords: Metaverse Based Learning; Quasi-Experimental Design; Second Life; Blended Learning; Online Learning.